The research trends of ferroptosis in diabetes: a bibliometric analysis - Xiong, Liyuan; Hu, Faquan; Li, Zhengpin; Zhou, Xuemei; Zheng, Yujiao (Frontiers in Public Health, 2024)
Objective: Exploring the mechanism of ferroptosis as a potential avenue for investigating the pathogenesis and therapeutic outlook of diabetes mellitus and its complications has emerged as a focal point within recent years. Herein, we employ a bibliometric approach to delineate the current landscape of ferroptosis research in the context of diabetes mellitus. Our objective is to furnish insights and scholarly references conducive to the advancement of comprehensive investigations and innovations in related domains.We included studies on ferroptosis in diabetes, obtained from the Web of Science Core Collection. All publications were transported in plaintext full-record format and were analyzed by CiteSpace 6.2.R4 for bibliometric analysis.Results: 448 records that met the criteria were included. The publications released during the initial three years were relatively small, while there was a sudden surge of publications published in 2022 and 2023. Representing 41 countries and 173 institutions, China and Wuhan University led the research on ferroptosis in diabetes.The author with the highest number of published papers is Zhongming Wu, while Dixon SJ is the most frequently cited author. The journal with the highest number of co-citations is Cell. The most common keywords include oxidative stress, cell death, lipid peroxidation, and metabolism. Extracted keywords predominantly focus on NLRP3 inflammatory, diabetic kidney disease, mitochondria, iron overload, and cardiomyopathy.The escalating recognition of ferroptosis as a potential therapeutic target for deciphering the intricate mechanisms underlying diabetes and its complications is underscored by a noteworthy surge in relevant research publications. This surge has catapulted ferroptosis into the spotlight as a burgeoning and vibrant research focus within the field.